Examining the Colonial Legacies of the Hunterian’s Mineralogical and Petrological Collection: New Perspectives on Geoscience Collections - Erika Anderson (Museum & Society)
The origin of the Hunterian Museum and Art Gallery’s mineralogical and petrological collection can be traced back to Sir William Hunter’s bequest of his collections to the University of Glasgow upon his death in 1783. Examination of the collection’s colonial legacies is only in its nascent stages, reflecting that the scrutiny of colonial legacies is still in its infancy in geoscience museums. Here I review the history of the collection, its composition and usage, and I put those factors into the broader perspective of museums’ colonial legacies.